2020
DOI: 10.1042/bsr20191764
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA ARAP1-AS1 accelerates cell proliferation and migration in breast cancer through miR-2110/HDAC2/PLIN1 axis

Abstract: Breast cancer (BC) poses a great threaten to women health. Numerous evidences suggest the important role of long non-coding RNAs (lncRNAs) in BC development. In the present study, we intended to investigate the role of ARAP1-AS1 in BC progression. First of all, the GEPIA data suggested that ARAP1-AS1 was highly expressed in breast invasive carcinoma (BRAC) tissues compared with the normal breast tissues. Meanwhile, the expression of ARAP1-AS1 was greatly up-regulated in BC cell lines. ARAP1-AS1 knockdown led t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…Moreover, lncRNA ARAP1-AS1 is also highly expressed in breast invasive carcinoma tissues, and the expression of lncRNA ARAP1-AS1 is significantly upregulated in breast cancer cell lines. The down-regulation of lncRNA ARAP1-AS1 expression leads to inhibition of breast cancer cell proliferation, enhanced apoptosis, and blocked migration (19). In the present study, it was found that lncRNA ARAP1-AS1 was significantly up-regulated in lung cancer tissues and cells, and knocking down of lncRNA ARAP1-AS1 can significantly inhibit cell proliferation and clonal formation.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Moreover, lncRNA ARAP1-AS1 is also highly expressed in breast invasive carcinoma tissues, and the expression of lncRNA ARAP1-AS1 is significantly upregulated in breast cancer cell lines. The down-regulation of lncRNA ARAP1-AS1 expression leads to inhibition of breast cancer cell proliferation, enhanced apoptosis, and blocked migration (19). In the present study, it was found that lncRNA ARAP1-AS1 was significantly up-regulated in lung cancer tissues and cells, and knocking down of lncRNA ARAP1-AS1 can significantly inhibit cell proliferation and clonal formation.…”
Section: Discussionsupporting
confidence: 53%
“…Furthermore, studies have shown that the non-coding RNA, ARAP1 antisense RNA 1 (ARAP1-AS1), can markedly affect the occurrence and development of other tumors, including bladder, colorectal, and breast cancers (17)(18)(19). However, the expression level, biological function, and molecular function of lncRNA ARAP1-AS1 in lung cancer tissues are still unclear.…”
Section: Original Articlementioning
confidence: 99%
See 1 more Smart Citation
“…High levels of LEP expression were associated with good prognosis in our study, which differed from an earlier report indicating LEP overexpression in BC [ 31 ]. PLIN1 promotes BC cell proliferation and migration [ 32 ]. CAV1 plays a key role in the stress response of BC cells by regulating lysosomal function and autophagy [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al suggested that the lncRNA TUSC8 may affect epithelial-mesenchymal transition (EMT)-associated protein levels by functioning as a ceRNA of myosin regulatory light chain interacting protein (MYLIP) as it binds miR-190b-5p, leading to the suppression of breast cancer progression [ 19 ]. Lu et al found that lncARAP1-AS promotes tumorigenesis by enhancing the proliferative and migratory abilities of breast cancer cells by modulating the miR-2110/HDAC2/PLIN1 axis [ 20 ]. However, there are different breast cancer subtypes, including HER2-positive breast cancer, luminal A and B breast cancer, and TNBC, and comprehensive studies on the ceRNA networks in each breast cancer subtype are limited, particularly regarding the identification of their specific molecular mechanisms.…”
Section: Discussionmentioning
confidence: 99%